Survei Motivasi Aktivitas Pendakian Gunung Puthuk Gragal Sebagai Edukasi Olahraga Rekreasi - Isna Muthi’ Atus Salmah; Hijrin Fithroni; Andun Sudijandoko; Muhammad Dzul Fikri (STIKes Ibnu Sina Ajibarang, 2024)
This research described a planned attempt to investigate the intrinsic and extrinsic motivation of climbers who are hiking on Mount Puthuk Gragal, located in Cembor village, Pacet district, Mojokerto regency. In conducting this research, the researcher applied a combination between quantitative descriptive and survey method. Whereas, by using purposive sampling, the researcher selected 60 respondents as the samples and gave a questionnaire that consisted of 22 questions. Furthermore, the research indicators included intrinsic and extrinsic. The outcome showed the motivation of climbers who were hiking on Mount Phutuk Gragal for recreational sport education. It can be concluded that climbers were more extrinsically motivated by 80.02% than intrinsically motivated by 78.76%. The average calculation for each type of motivation showed that the intrinsic motivation of hiking on Mount Puthuk Gragal for recreational sport consisted of indicators: necessity of 77.50% in the high category, expectation of 87.50% in the very high category, curiosity of 84.45% in the very high category and pleasure of 65.58% in the High category, while extrinsic motivation consisted of indicators: facilities of 79.62% in the high category and beauty of 80.42% in the high category. Based on the data above, it can be concluded that the motivation of climbers when hiking on Mountain Puthuk Gragal based on high necessity, high expectation, high curiosity, high pleasure, high facility, and high beauty.